Neuro-Oncology Practice Clinical Debate: long-term antiepileptic drug prophylaxis in patients with glioma - Stocksdale, Brian (Neurooncol Pract, 2020)
Patients with primary brain tumors often experience seizures, which can be the presenting symptom or occur for the first time at any point along the illness trajectory. In addition to causing morbidity, seizures negatively affect independence and quality of life in other ways, for example, by leading to loss of driving privileges. Long-term therapy with antiepileptic drugs (AEDs) is the standard of care in brain tumor patients with seizures, but the role of prophylactic AEDs in seizure-naive patients remains controversial. In this article, experts in the field discuss the issues of AED efficacy and toxicity, and explain their differing recommendations for routine use of prophylactic AEDs.